2016
DOI: 10.1371/journal.pone.0148518
|View full text |Cite
|
Sign up to set email alerts
|

Colonization of Beef Cattle by Shiga Toxin-Producing Escherichia coli during the First Year of Life: A Cohort Study

Abstract: Each year Shiga toxin-producing Escherichia coli (STEC) are responsible for 2.8 million acute illnesses around the world and > 250,000 cases in the US. Lowering the prevalence of this pathogen in animal reservoirs has the potential to reduce STEC outbreaks in humans by controlling its entrance into the food chain. However, factors that modulate the colonization and persistence of STEC in beef cattle remain largely unidentified. This study evaluated if animal physiological factors such as age, breed, sex, and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 31 publications
5
42
0
Order By: Relevance
“…Component 23 (p = 0.025) is most likely describing a protective effect of increasing age which has been previously observed 41 . It also highlights a correlation between increasing age, dirtiness and firm faeces.…”
Section: Exploring Interdependence and Covariation Using Principal Cosupporting
confidence: 57%
“…Component 23 (p = 0.025) is most likely describing a protective effect of increasing age which has been previously observed 41 . It also highlights a correlation between increasing age, dirtiness and firm faeces.…”
Section: Exploring Interdependence and Covariation Using Principal Cosupporting
confidence: 57%
“…In adults animals, prevalence of STEC decrease while the commensal microflora increase its diversity, possibly influenced by diet of the animals which changes as the animal weans, grows and begins to incorpore pasture, or specific diet according the production system (Mir et al, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Some studies did not find the sex of the calf to be significantly associated with shedding (Mir et al 2015(Mir et al , 2016, others found that shedding was more intense in herds having many bull calves (Nielsen et al 2002) and other authors reported that higher E. coli shedding can be seen on farms that harbor female breeding cattle (Chase-Topping et al 2007). In one study, castration decreased the super-shedding of E. coli O157, which was significantly higher in bulls as compared to steers, despite the fact that the prevalence of the bacterium was comparable between the two animal groups (Jeon et al 2013).…”
Section: Cattle-specific Factors Involved In Super-sheddingmentioning
confidence: 99%